Localization for autonomous car using deep learning - Lee, Woon Shin (2023)
Self-driving car, which is also known as autonomous vehicle or robotic car that all car manufacturer that wish to develop into a fully self-driving car. They are trying to develop and achieve higher level of automated driving. Localization is part of subsystem in the automated driving, which is most of the autonomous or robotic car manufacturer trying to improve and develop it into fully self-driving car. Localization in autonomous car can be defined as the process of locating the current position of vehicle. Localization able to let autonomous car know where it is at the current position of it and navigate the ways to destination. It can let user to drive less, avoid car accident when we are inside the car to our destination. To reach this goal, many cars manufacturer or technology company has worked in this area for years to solve the obstacles in the way to achieve next level of automated driving. In this paper, it aims to focus on how the localization works with the proposed methods. The proposed method will use the OpenCV computer vision algorithms and other solutions to solve the localization problem.